Gaya Kepemimpinan Walikota Banjar Periode 2018 – 2023 - Rifal Amalindi; Erlan Suwarlan; Asep Nurwanda (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
In the context of regional autonomy, the leadership of the regional head is a determining factor in realizing quality public services. This study examines the leadership style of the Mayor of Banjar for the 2018–2023 period in implementing bureaucratic reform. The research method used is descriptive qualitative with primary and secondary data sources. The results of the analysis show that although various efforts have been made such as cross-sector coordination and participatory communication, there are a number of obstacles in achieving program targets and bureaucratic performance. This finding highlights the importance of strengthening democratic leadership and human resource management in supporting the implementation of regional work programs optimally.